2011
DOI: 10.1016/j.addbeh.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Alcohol Identity Implicit Associations Test (AI-IAT)

Abstract: Alcohol identity is the extent to which an individual perceives drinking alcohol to be a defining characteristic of his or her self-identity. Although alcohol identity might play an important role in risky college drinking practices, there is currently no easily administered, implicit measure of this concept. Therefore we developed a computerized implicit measure of alcohol identity (the Alcohol Identity Implicit Associations Test; AI-IAT) and assessed its reliability and predictive validity in relation to ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 42 publications
8
60
2
Order By: Relevance
“…The emphasis on drinking identity stems from a reformulation of the theory of planned behavior (original: Ajzen, 1991;reformulation: Fekadu and Kraft, 2001) that posited and ultimately demonstrated that including measures of how strongly one identifi es with a (hazardous) behavior increases the predictability of that behavior. With respect to implicit drinking identity specifi cally, three recent studies (e.g., Gray et al, 2011;Lindgren et al, 2013aLindgren et al, , 2013b of undergraduates in three different regions of the United States have found support for implicit drinking identity as a unique predictor of alcoholrelated outcomes. Moreover, the two studies by Lindgren et al (2013aLindgren et al ( , 2013b) also found that implicit drinking identity associations, when compared with other implicit alcoholrelated associations, were the strongest and most consistent predictors of alcohol-related outcomes (e.g., self-reported consumption, cravings, and problems).…”
Section: Dual-process Models Implicit Associations and Drinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…The emphasis on drinking identity stems from a reformulation of the theory of planned behavior (original: Ajzen, 1991;reformulation: Fekadu and Kraft, 2001) that posited and ultimately demonstrated that including measures of how strongly one identifi es with a (hazardous) behavior increases the predictability of that behavior. With respect to implicit drinking identity specifi cally, three recent studies (e.g., Gray et al, 2011;Lindgren et al, 2013aLindgren et al, , 2013b of undergraduates in three different regions of the United States have found support for implicit drinking identity as a unique predictor of alcoholrelated outcomes. Moreover, the two studies by Lindgren et al (2013aLindgren et al ( , 2013b) also found that implicit drinking identity associations, when compared with other implicit alcoholrelated associations, were the strongest and most consistent predictors of alcohol-related outcomes (e.g., self-reported consumption, cravings, and problems).…”
Section: Dual-process Models Implicit Associations and Drinkingmentioning
confidence: 99%
“…Although a variety of implicit alcohol-related associations have been investigated, implicit drinking identity associations (e.g., associations with the self and drinking or with the self and alcohol) have recently emerged as promising predictors of risky drinking behavior in young adults (Gray et al, 2011;Lindgren et al, 2013aLindgren et al, , 2013b. The emphasis on drinking identity stems from a reformulation of the theory of planned behavior (original: Ajzen, 1991;reformulation: Fekadu and Kraft, 2001) that posited and ultimately demonstrated that including measures of how strongly one identifi es with a (hazardous) behavior increases the predictability of that behavior.…”
Section: Dual-process Models Implicit Associations and Drinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that implicit identification has been found to predict unique variance in drinking outcomes (Gray, LaPlante, Bannon, Ambady & Shaffer, 2011;Lindgren et al, 2013) as well as length of time spent in rehabilitation centres for alcohol and drug dependence (Wolff et al, 2015). The current study did not support the idea that implicit identification with drug use can predict future drug related behaviour.…”
Section: Limitations and Future Directionscontrasting
confidence: 53%
“…Many of the analyzed articles evaluated the validity of the methods of IAC assessment and found that: the IAT, the Extrinsic Affective Simon Task (EAST;De Houwer, 2003), the Affect Misattribution Procedure (AMP; Payne, Cheng, Govorun & Stewart, 2005), the Affective Priming Paradigm (APP; Fazio et al, 1986), and the Word Association Test (Stacy, Leigh & Weingardt, 1994) were valid methods to assess IAC (Gray, LaPlante, Bannon, Ambady & Shaffer, 2011;Houben, Rothermund & Wiers, 2009;Lindgren, Westgate, Kilmer, Kaysen & Teachman, 2012;Lindgren, Hendershot, Neighbors, Blayney & Otto, 2011;Ostafin & Palfai, 2006;Payne, Govorun & Arbuckle, 2008).…”
Section: Topic 1: Methods Of Iac Assessmentmentioning
confidence: 99%